(untitled) (Fiep Bulletin - online, 2013)
The objective of the study was to comprehend the sentiments that mothers have when faced with their children interned in the NICU and the moments that they occur. Seven mothers were interviewed in a teaching maternity hospital located in the Northeast of Brazil. The mothers´ depositions were analyzed by the technique of analysis of content and the theory of Interaction Symbolism. The sentiments of deception emerged because at the loss of the “idealized baby” image; guilt and impotency because of the critical situation of the baby; sadness and shock when facing the NICU environment; happiness and joy at the initial interaction with the baby; faith and hope regarding the future of the baby; and confidence in the health team. It is concluded that when faced with the internment of their babies in the NICU, the mothers experience moments full of sentiments that are both stressful and joyful. When the nurse identifies the moments that revive these sentiments, interventions can be implemented to ameliorate or support these emotions.